Evaluating the Propagation of Uncertainties in Biologically Based Treatment Planning Parameters - Barry, Miriam A.; Hussein, Mohammad; Schettino, Giuseppe (Frontiers in Oncology, 2020)
Biologically based treatment planning is a broad term used to cover any instance in radiotherapy treatment planning where some form of biological input has been used. This is wide ranging and the simpler forms (e.g. fractionation modification/optimisation) have been in use for many years. However, there is a reluctance to use more sophisticated methods that incorporate biological models either for plan evaluation purposes or for driving plan optimisations. This is due to limited data available regarding the uncertainties in these model parameters and what impact these have clinically. This work aims to address some of these issues and to explore the role that uncertainties in individual model parameters have on the overall TCP/NTCP calculated, those parameters that have the largest influence and situations where extra care must be taken. In order to achieve this, a software tool was developed which can import individual clinical DVH’s for analysis using a range of different TCP/NTCP models. On inputting individual model parameters an uncertainty can be applied. Using a normally distributed random number generator, distributions of parameters can be generated, from which TCP/NTCP values can be calculated for each parameter set for the DVH in question. These represent the spread in TCP/NTCP parameters that would be observed for a simulated population of patients all being treated with that particular dose distribution. A selection of clinical DVHs were assessed using published parameters and their associated uncertainties. A range of studies were carried out to determine the impact of individual parameter uncertainties including reduction of uncertainties and assessment of what impact fractionation and dose has on these probabilities.